Comparative Study on Seismic Behavior of Regular and Irregular Building in Sloping Ground - Poudel , Prakash; Adhikari, Badri (Himalayan Journal of Applied Science and Engineering, 2025)
Nepal is situated in a highly earthquake-prone region. Majority of land is covered by hilly and mountainous topography. Due to the scarcity of plain ground, urbanization has rapidly increased with the construction of buildings on sloping ground. These buildings constructed in sloping ground are susceptible to severe damage due to earthquake. The aim of this study is to compare seismic behavior of different configuration of building built in hill slope: step back (SB), step back set back (SBSB), split foundation (SF), split foundation set back (SFSB) buildings having regular and irregular shape considering soil effect (SSI) and compared with the fixed base and with the building constructed in Plain ground (PG).  To fulfill this aim selection of 20 distinct models, with 10 adhering to regular shapes and the remaining 10 exhibiting irregular configurations. Moreover, half of the models incorporate fixed bases, while the other half considers the impact of soil. All models maintain consistent material properties and other parameters. The natural slope of the ground for structures on sloping terrain is set at 300. Stiffness of soil is assigned as a point spring to the base of structure for introducing effect of soil. The building models are constructed using Finite Element Analysis (FEM) software, specifically ETABS version 16.2.1 and the non-linear time history analysis is done by using Gorkha earthquake, Empirical earthquake and Turkey earthquake time history function. NBC 105:2020 code is used for this seismic analysis. Finally the seismic performance of all the buildings is evaluated by determining fundamental time period, base shear, top story displacement, inter story drift and torsional irregularity ratio by  the use of FEM software ETABS and these values were compared with different building configuration and the configuration more susceptible and less susceptible to earthquake is determined. The study concludes that on sloping ground SF is found to be more vulnerable while   SBSB building performs better than other building. The incorporation of soil effect has substantial impact on building performance and due to flexibility induced in base the top displacement and time period of flexible base structure has increased while the base shear is decreased by considering soil effect.